Efektivitas Penggunaan Buku Cerita Rakyat Lokal dalam Meningkatkan Kemampuan Literasi Anak Kelompok B - Salsabilla, Tiara; Aryani, Nini; Wilyanita, Nopa (PT. Riset Press International, 2026)
Early literacy skills serve as a crucial foundation for cognitive and language development. This study aims to describe the improvement of literacy skills in children aged 5-6 years through the use of Riau folklore storybooks. The research method employed was Classroom Action Research (CAR) conducted in two cycles. The subjects consisted of 11 children (7 boys and 4 girls) in Group B of TK Mustika Bunda Pekanbaru. Data were collected through observation and documentation, then analyzed using descriptive comparative techniques. The results showed a significant increase in children's literacy skills. During the pre-cycle stage, the majority of children (63.6%) were in the